Winners of the Governor’s Prize 2021 Album-catalogue about Baikal - Chertilov, Alexei (project baikal, 2022)
The article presents an illustrated research album-catalogue “Baikal on postcards. 1898-1917. Historical and bibliographical album-catalogue” which received the Governor’s Prize 2021. The sites included in the catalog are briefly characterized. The innovative character and importance of the project is emphasized. The book review was published in Project Baikal journal (Medvedev, 2020).
Keywords: Baikal; collectors; Circum-Baikal railroad; catalogue; Irkutsk; Region Governor's Prize